2017
DOI: 10.3390/ijms18010155
|View full text |Cite
|
Sign up to set email alerts
|

Broad-Spectrum Inhibition of the CC-Chemokine Class Improves Wound Healing and Wound Angiogenesis

Abstract: Angiogenesis is involved in the inflammation and proliferation stages of wound healing, to bring inflammatory cells to the wound and provide a microvascular network to maintain new tissue formation. An excess of inflammation, however, leads to prolonged wound healing and scar formation, often resulting in unfavourable outcomes such as amputation. CC-chemokines play key roles in the promotion of inflammation and inflammatory-driven angiogenesis. Therefore, inhibition of the CC-chemokine class may improve wound … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 50 publications
(49 reference statements)
0
22
0
1
Order By: Relevance
“…To further investigate the molecular mechanism underlying CCL5 secretion by CD8 + T cells in low androgen conditions, we focused on the signaling cascade downstream of cGMP/PKG. Several studies indicated that NF‐κB plays an important regulatory role in the immune response, and that cGMP/PKG activation inhibited NF‐κB in hyperthermia‐exposed MCF‐7 cells, resulting in apoptosis . In this study, we showed, for the first time, that the cGMP/PKG pathway regulates the function of CD8 + T cells by controlling NF‐κB p65 phosphorylation, which affects the secretion of CCL5.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…To further investigate the molecular mechanism underlying CCL5 secretion by CD8 + T cells in low androgen conditions, we focused on the signaling cascade downstream of cGMP/PKG. Several studies indicated that NF‐κB plays an important regulatory role in the immune response, and that cGMP/PKG activation inhibited NF‐κB in hyperthermia‐exposed MCF‐7 cells, resulting in apoptosis . In this study, we showed, for the first time, that the cGMP/PKG pathway regulates the function of CD8 + T cells by controlling NF‐κB p65 phosphorylation, which affects the secretion of CCL5.…”
Section: Discussionmentioning
confidence: 49%
“…NF‐κB is a transcription factor playing a key role in inflammation, and several studies have demonstrated that it is regulated by the NO/cGMP/PKG signaling pathway . Therefore, we analyzed the phosphorylation of NF‐κB p65 subunit in the nuclear fraction of Molt‐3 cells treated with tadalafil/Sp‐8‐Br‐PET‐cGMP by Western blot analysis, which revealed that phospho‐NF‐κB p65 was downregulated by the drugs, but PKG inhibitor KT5823 (100 nM) reversed the effect (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…It is well established that prolonged inflammation and production of pro-inflammatory chemokines can lead to nonhealing wounds, and broad-spectrum chemokine inhibitors are therefore tried to limit wound inflammation. The chemokine inhibitor 35K, which inhibits the entire class of CC-chemokines, enhanced wound closure and neovascularization in murine wounds [81]. How this approach influence on wound infections needs to be further established.…”
Section: Chemokinesmentioning
confidence: 99%
“…In a recent study by Ridiandries et al . , topical application of the broad‐spectrum CC chemokine inhibitor was found to decrease wound CCL5 and CCL2 protein levels, leading to improved wound healing and neovascularization during the early stages, demonstrating thus the importance of the modulation of these chemokines in the tissues. In this study, wounds treated with this inhibitor showed significantly lower expression of the p65 subunit of NF‐ κ B, an important inflammatory transcription factor for increased expression of the pro‐angiogenic and prorepair cytokine TGF‐ β in the wound, demonstrating that inhibition of CC chemokines may be beneficial for the induction of wound healing.…”
Section: Introductionmentioning
confidence: 98%